Dengue-4 false negative results by Panbio (R) Dengue Early ELISA assay in Brazil - Colombo, Tatiana Elias [UNESP]; Vedovello, Danila; Araki, Carlos Shigueru; Cogo-Moreira, Hugo; Penha dos Santos, Izalco Nuremberg; Negri Reis, Andreia Francesli; Costa, Fabiana Rodrigues; Arao Antonio Cruz, Lilian Elisa; Casagrande, Liane; Regatieri, Livia Jose; Ferreira Junior, Jurandir; Morais Bronzoni, Roberta Vieira de; et al. (Elsevier B.V., 2013)
Background: Dengue is a serious public health problem in numerous countries. The ability to rapidly diagnosis dengue is important for patient triage and management. Detection of dengue viral protein, NS1, represents a new approach to dengue diagnosis.Objective: The present study aims to evaluate if there are false negative results using the NS1 Ag rapid assay (Panbio (R) Dengue Early ELISA) in two different epidemiological situations (epidemic and non-epidemic).Study design: 220 serum samples from patients with clinical symptoms of classical dengue fever were tested by NS1 antigen capture ELISA and Multiplex-Nested-PCR.Results: In samples collected in a non-epidemic period we found a 100% agreement of ELISA and RTPCR in dengue negative samples and 85% agreement of ELISA and RT-PCR in dengue positive samples. But when we tested samples during an epidemic period (large DENV-4 outbreak) we found 15% false negative results (p<0.05) in dengue negative samples.Conclusions: Due to false negative results for DENV-4, the sole use of the Panbio Dengue Early ELISA assay as a screening method for monitoring circulating dengue serotypes must be reevaluated. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Dengue; NS1 Ag rapid assay; False negative results